Digital imaging of artefacts : developments in methods and aims - Kelley, Kate,; Wood, Rachel K. L., (Access archaeology., 2018)
This title features the proceedings from a workshop held at Wolfson College, Oxford in 2017. In light of rapid technological developments in digital imaging, this volume will inform specialist and general readers about some of the ways in which imaging technologies are transforming the study and presentation of archaeological and cultural artefacts.